One with the Universe (2021)
What if the substance and the intention of the Universe come from a deeper reality than the material one we normally perceive with our minds and senses One with the Universe is an immersive installation that emerges from the deep feeling of connectedness between beings, objects, events and spaces. In a conscious and interconnected universe there is a reason to feel connected to the people and to the world; to feel loved, hopeful and happy and at peace with oneself and others. One with the Universe is an immersive digital environment that uses a Kinect sensor for real-time interaction. The central experience is that of the immersant who discovers varying levels of responsiveness and interaction modes and through subjective experiences is nudged into a state of consciousness.